Bis(2-aminopyrimidine-κN (1))diaquadinitrato-κO;κ(2) O,O′-cadmium(II) monohydrate - Tai, Xi-Shi (International Union of Crystallography, 2008)
In the title compound, [Cd(NO(3))(2)(C(4)H(5)N(3))(2)(H(2)O)(2)]·H(2)O, the Cd atom is seven-coordinated by two 2-aminopyrimidine molecules, two water molecules, one bidentate nitrate anion and one monodentate nitrate anion. A network of N—H⋯O, N—H⋯N and O—H⋯O hydrogen bonds helps to consolidate the crystal structure.